Case Report: Two Genetically Distinct Choroidal Melanomas in the Same Eye Treated with Endolaser Therapy. Issue 9 (25th September 2021) - Saigal, Khushi; El Hamichi, Sophia; Gold, Aaron S.; Murray, Timothy G.
Abstract : Supplemental digital content is available in the text. Abstract : SIGNIFICANCE: This case report highlights the merits of using fine needle aspiration biopsy to obtain gene expression profiling of individual choroidal melanomas when more than one tumor arises in the same eye. It is also the first such case to document laser ablation therapy as the primary treatment. PURPOSE: This report describes a case of two primary choroidal melanomas with different genetic profiles in the same eye. CASE REPORT: An 80-year-old man presented to the office with a neoplasm of uncertain behavior in the left eye. The patient's visual acuity and IOP in the left eye, respectively, at the time of his first visit to the office were 20/25 and 8 mmHg. A dilated fundus examination revealed that there were two choroidal lesions in the left eye. The macular lesion was classified as type 1A, and the ciliochoroidal lesion was classified as type 1B. The patient underwent a vitrectomy of the left eye, followed by endolaser ablation of the tumors. The patient was also injected with bevacizumab. To date, the patient is free of known metastasis. Most recently, his visual acuity and IOP in the left eye were 20/30 and 14 mmHg, respectively. CONCLUSIONS: Although rare, multiple melanomas in the same eye may have differing genetic profiles, which may alter prognosis and management, depending on the class of tumor detected.